Barron's SAT - Green, Sharon Weiner and Wolf, Ira K. (Lahore Jahangir Books, 2009)
The newly revised edition presents a diagnostic test and five full-length practice tests with all questions answered and explained, test-taking tactics for the exam as a whole, special strategies for each part of the test, and more.
Include Color Illustrations
Keywords: SAT (Educational test) -- United States